Pengembangan LKPD Materi Kubus dan Balok Menggunakan Konteks Pribadi untuk Peserta Didik Kelas VIII - Satiti, Wisnu Siwi; Khotimah, Khusnul; Rosyid, Moh. Ali (Exact Papers in Compilation (EPiC), 2021)
With the increasing number of real-life situations that require some level of mathematical understanding, this shows that mathematical concepts have an important role in everyday life. One of the mathematical studies that is widely used in everyday life is geometry. Many objects in everyday life are geometric shapes, including cubes and blocks. However, the practice of learning on cube and block material has not accommodated these needs, that is a learning that accommodates everyday situations experienced by students. Considering this, in this study, learning media was developed in the form of Student Worksheets (LKPD) which were arranged using the personal context of students on cube and block material. The target of this research is students of class VIII junior high school (SMP/MTs). This study uses the Research and Development (R&D) method with the ADDIE model. This study aims to develop LKPD for Cube and Block Materials Using Personal Context for Students grade VIII. The results show that the LKPD is valid and practical. The results of the product implementation show that the use of this LKPD supports students' understanding on concept of cube and block. The use of LKPD also received a "good" response by students.